Analysis of the situation of the child and adolescent working population in the municipality of Bucaramanga (2001-2011). - Sánchez – Reyes, Jimmy (Universidad Francisco de Paula Santander, 2018)
In Colombia, child labor is a growing social problem that concerns society. Child labor is associated with activities performed by minors, such as any kind of paid or unpaid work, full-time occupations, chores that interfere with school attendance, exploitative or harmful tasks, and work that violates national or international laws on child and adolescent labor. Bucaramanga, a Colombian city, has also seen an increase in child labor. Child labor has negative consequences on the health of minors and, in the future, on the adult population. In addition, it hinders education and increases poverty gaps. The results of a survey conducted directly with working children indicate that most children work in the commercial sector and many indicated that they only worked for the season. 47% do not live with both parents and 13% do not live with either parent. Despite working, most still attend school. 64% work for a family member who is within their immediate family or is a close relative. Only 54% receive payment for their work. On average, they receive $425,000.